MicroRNA-21 as a biomarker in terminal stage oral squamous cell carcinoma (OSCC) in the South Indian population - Chevuru Sai Shreya Reddy; Ashikha Shirin Usman P.P; Dhanraj M. Ganapathy; Ameya K.P.; Durairaj Sekar (Oral Oncology Reports)
Objective: Micro RNA-21(miR-21) earlier identified as high amount in different types of cancer. They are non-coding sequences with limited no of nucleotides and play important role in regulation of genes. Predicting the miR-21 levels could act as biomarkers for Oral Squamous Cell Carcinoma (OSCC). OSCC include every cancer found in the oropharynx and oral cavity. The current study retrieved mature sequences of miRNA from database- NCBI and used to find miRNA from OSCC. Its coming among the list of most prevalent malignancy in world, especially in India. This paper primarily focuses on miR-21 expression analysis as a biomarker of oscc in the South Indian population. Materials and methods: miR-21 secondary structure is predicted using Bioinformatics tools from OSCC. Sequence was extracted from NCBI 25 OSCC samples and adjacent normal tissues were collected, and RNA were extracted, quantified, and reverse transcribed after doing histopathological analysis in cancer tissues. Expression of miR-21 done using qRT-PCR from the cDNA obtained. Utilizing statistical software, the relationship between the expression of miR-21 and the clinicopathological characteristics of OSCC was examined. Level of expression of genes in both cancer cells and normal cells are also analysed using graphical method. Result: miR-21 secondary structure is predicted by applying mature sequence of miRNA. The values obtained by statistical analysis showed expression of miR-21 is increased in oscc samples compared to normal cells. Conclusion: Thus miR-21 is a potential biomarker associated with OSCC. Study also elucidated positive correlation between miR-21 in oscc samples.